URGENSI KOMUNIKASI EFEKTIF DALAM PROSES TRANSFER INFORMASI DI PERPUSTAKAAN PERGURUAN TINGGI - Ramayanti, Rory (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2018)
ABSTRACT This paper describes how the role of effective communication in speeding up the process of transfer of information in the College Library. There are three issues into the discussion in this paper; (i) effective communication in the process of transfer of information with assertive communication by considering personal rights between librarians and users; (ii) how to create effective communication between librarians with the user by means of the receiver understand the message conveyed, can establish a good relationship between librarians and users, the message shoving on a response desired message recipients; (iii) This paper outlines the third obstacle in conducting effective communication among them is a different background, signals, communication situation, quality of the content of the message, writing skills, speaking skills, the skills of listening, reading skills